PENGARUH CAMPURAN MEDIA TANAM GAMBUT DENGAN PODSOLIK MERAH KUNING TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PEMBIBITAN UTAMA - Foller, Rudi; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to determine the influence of growing media mixture of peat and Red Yellow Podzolic (RYP) and to get best growing media to palm oil growth seedlings (Elaeis guinensis Jacq) in the main nursery. This research conducted on March to July 2016. This study was an experiment using of completely randomized design (CRD), which consists of 7 treatments with 4 replications. The treatments were growing media comparison of peat and red yellow podzolic such as 1: 0 (T1), 0:1 (T2), 1:1 (T3), 2:1 (T4), 1:2 (T5), 1:3 (T6), 3:1 (T7), Parameters measured were increase of height plant, the number of leaves, diameter of hump, and broad leaves. Observation of data were analized statistically with ANOVA and Duncan's multiple range test level of 5%. The results showed that growing media mixture of peat and red-yellow podzolic influence to palm oil growth in main nursery. Growing media mixture of peat and red yellow podzolic 3:1 (T7) significantly increase of hump diameter and broad leaves of palm oil seedling. Keywords: Peat soil, mineral soil, Elaeis guineensis jacq